Employee benefit planning - Rosenbloom , Jerry S. (Pearson Custom Publishing, 1991)
In its annual publication, Employee benefits, the United States Chamber of Commerce estimated that employee benefits approximate 39 percent of payroll. So it is clear that employee benefits represent an important and growing fiel of study.